LASER as a tool for surface modification of dental biomaterials: A review - Runki Saran; Kishore Ginjupalli; Sajan D. George; Santhosh Chidangil; Unnikrishnan V K (Heliyon, 2023)
In recent years, the application of lasers for modifying the surface topography of dental biomaterials has received increased attention. This review paper aims to provide an overview of the current status on the utilization of lasers as a potential tool for surface modification of dental biomaterials such as implants, ceramics, and other materials used for restorative purposes. A literature search was done for articles related to the use of lasers for surface modification of dental biomaterials in English language published between October 2000 and March 2023 in Scopus, Pubmed and web of science, and relevant articles were reviewed.Lasers have been mainly used for surface modification of implant materials (71%), especially titanium and its alloys, to promote osseointegration. In recent years, laser texturing has also emerged as a promising technique to reduce bacterial adhesion on titanium implant surfaces. Currently, lasers are being widely used for surface modifications to improve osseointegration and reduce peri-implant inflammation of ceramic implants and to enhance the retention of ceramic restorations to the tooth. The studies considered in this review seem to suggest laser texturing to be more proficient than the conventional methods of surface modification. Lasers can alter the surface characteristics of dental biomaterials by creating innovative surface patterns without significantly affecting their bulk properties. With advances in laser technology and availability of newer wavelengths and modes, laser as a tool for surface modification of dental biomaterials is a promising field, with excellent potential for future research.